2022
DOI: 10.12793/tcp.2022.30.e13
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open-label, single-dose, two-way crossover study to assess the pharmacokinetics between two tablets of fixed-dose combination formulation with raloxifene and cholecalciferol and concomitant administration of each agents in healthy male volunteers

Abstract: A new fixed-dose combination (FDC) formulation of raloxifene 60 mg and cholecalciferol 800 IU was developed to improve the medication compliance and overall efficacy of raloxifene treatment in postmenopausal osteoporosis patients. The aim of this study was to compare the pharmacokinetics between two tablets of FDC formulation of raloxifene/cholecalciferol and the two products administered concomitantly at respective doses. This randomized, open-label, single-dose, two-treatment, two-way crossover study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The intersubject variability (%CV) values of AUC 0-t , AUC 0-∞ , C max , and t 1/2 obtained from the conventional formulation in our study were comparable to the values from our earlier studies (36.9%-50.8%, 44.3%-49.0%, 40.5%-48.9%, and 37.4%-64.8%, respectively). 15,18 Although this study indicated that the test formulation had larger intersubject %CV values of AUC 0-t , AUC 0-∞ , C max , and t 1/2 (53.4%, 101.8%, 62.6%, and 108.4%, respectively) than those from the reference formulation, the 90% CIs of the GMRs (test/reference) for AUC 0-t , AUC 0-∞ , and C max fell within the bioequivalence range, as presented in Table 3. The GMR (90% CI) for t 1/2 was 0.96 (0.86-1.07).…”
Section: Discussionmentioning
confidence: 99%
“…The intersubject variability (%CV) values of AUC 0-t , AUC 0-∞ , C max , and t 1/2 obtained from the conventional formulation in our study were comparable to the values from our earlier studies (36.9%-50.8%, 44.3%-49.0%, 40.5%-48.9%, and 37.4%-64.8%, respectively). 15,18 Although this study indicated that the test formulation had larger intersubject %CV values of AUC 0-t , AUC 0-∞ , C max , and t 1/2 (53.4%, 101.8%, 62.6%, and 108.4%, respectively) than those from the reference formulation, the 90% CIs of the GMRs (test/reference) for AUC 0-t , AUC 0-∞ , and C max fell within the bioequivalence range, as presented in Table 3. The GMR (90% CI) for t 1/2 was 0.96 (0.86-1.07).…”
Section: Discussionmentioning
confidence: 99%